2012
DOI: 10.1016/j.bbadis.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered cofactor binding affects stability and activity of human UDP-galactose 4′-epimerase: Implications for type III galactosemia

Abstract: Deficiency of UDP-galactose 4′-epimerase is implicated in type III galactosemia. Two variants, p.K161N-hGALE and p.D175N-hGALE, have been previously found in combination with other alleles in patients with a mild form of the disease. Both variants were studied in vivo and in vitro and showed different levels of impairment. p.K161N-hGALE was severely impaired with substantially reduced enzymatic activity, increased thermal stability, reduced cofactor binding and inability to rescue the galactose-sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Differential scanning fluorimetry was carried out essentially as previously described [39;40]. Protein samples were diluted in 10 mM HEPES, pH 8.8 to a final concentration of 5 μM and any ligands used were added at a final concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Differential scanning fluorimetry was carried out essentially as previously described [39;40]. Protein samples were diluted in 10 mM HEPES, pH 8.8 to a final concentration of 5 μM and any ligands used were added at a final concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…K161N is also very severely impaired kinetically, with the likely loss of the NAD cofactor. Interestingly, this mutant is thermally more stable than wildtype (18). …”
Section: Introductionmentioning
confidence: 92%
“…In addition, aggregation of HsGALE has been observed in cells expressing disease-associated variants (22). As yet, there are no small molecule therapies for any form of galactosemia, although it has been suggested that a “small molecule chaperone” approach may be viable since many of the mutations result in decreased protein stability (1, 15, 17, 18, 23-25). In order to implement such therapies, however, it is important to understand more about not just the structures of the proteins and the disease-associated variants but also the flexibility and dynamics of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of the protein at 280 nm results in a large tryptophan emission peak at ~330 nm. However, some of the emission transfers to the NAD + which emits at ~420 nm (McCorvie et al 2012). A similar effect was observed with FhGALE (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…GALE has been shown to be essential for normal development in Drosophila melanogaster (Daenzer et al 2012; Sanders et al 2010). Although the molecular pathology of type III galactosemia is not completely elucidated, the fundamental molecular cause has been shown to be protein misfolding which results in reduced enzymatic activity, reduced cofactor binding or an increased propensity to aggregate (Bang et al 2009; Chhay et al 2008; McCorvie et al 2011; McCorvie et al 2012; Timson 2005; Wohlers and Fridovich-Keil 2000). A reduction in GALE activity results in a build-up of galactose 1-phosphate, which is believed to be toxic in high concentrations (Mayes et al 1970; Tsakiris et al 2005).…”
Section: Introductionmentioning
confidence: 99%